KENDALI ORGANISASI TIM PRODUKSI PROGRAM â€œBANGUN PAGIâ€ DI 106,06 V RADIO JAKARTA - Agustine, Pingkan; Liliyana, Liliyana; Yuni Ani, Hani (Jurnal Akrab Juara, 2019)
This study aims to determine the control team of the Bangun Pagi production program organization. The proposed research statement is what control organizations do by the Bangun Pagi program production team. The theory that researchers use to obtain data using organizational control theory. The research method used is a descriptive qualitative approach with a post-positivism paradigm. The research subjects were program directors, producers and broadcasters in obtaining accurate data, and the object of research was the control of the production team of the Bangun Pagi program organization on Radio 106.06 V in Jakarta. Data collection obtained through in-depth interviews and participant observation carried out to key informants and informants. Other data obtained from documentation, informants, and various other data sources. The results of the study mentioned that the production team of the Bangun Pagi V Radio program carried out four concepts of the organizational control theory of Phillip Tompkins, George Cheney, and his colleagues consistently. The conclusion of this research is that the production team performs four concepts of control theory quite well, and it can be accounted for where the four concepts of this theory are the processes by which the production team performs in producing program events.